2021
DOI: 10.1155/2021/6615384
|View full text |Cite
|
Sign up to set email alerts
|

Altered Functional Connectivity in Children with ADHD Revealed by Scalp EEG: An ERP Study

Abstract: Attention deficit hyperactivity disorder (ADHD) is one of the most common neurodevelopmental brain disorders in childhood. Despite extensive researches, the neurobiological mechanism underlying ADHD is still left unveiled. Since the deficit functions, such as attention, have been demonstrated in ADHD, in our present study, based on the oddball P3 task, the corresponding electroencephalogram (EEG) of both healthy controls (HCs) and ADHD children was first collected. And we then not only focused on the event-rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…In children with ADHD, atomoxetine increases the activity of the parietal lobe (Bush et al, 2013), anodal tDCS improves working memory performance (Salehinejad et al, 2020), and dTMS increases the activity of the right parietal lobe and improves working memory performance (Bleich-Cohen et al, 2021). Lower connectivity of the IPL and the PPC is associated with ADHD symptoms, which are associated with weakness in the control of irrelevant auditory and visual stimuli and inattention symptoms (Chen et al, 2021;Kolodny et al, 2020;Salmi et al, 2020;Schneider et al, 2010;Schwerdtfeger et al, 2013).…”
Section: Bilateral and Central Parietal Lobementioning
confidence: 99%
“…In children with ADHD, atomoxetine increases the activity of the parietal lobe (Bush et al, 2013), anodal tDCS improves working memory performance (Salehinejad et al, 2020), and dTMS increases the activity of the right parietal lobe and improves working memory performance (Bleich-Cohen et al, 2021). Lower connectivity of the IPL and the PPC is associated with ADHD symptoms, which are associated with weakness in the control of irrelevant auditory and visual stimuli and inattention symptoms (Chen et al, 2021;Kolodny et al, 2020;Salmi et al, 2020;Schneider et al, 2010;Schwerdtfeger et al, 2013).…”
Section: Bilateral and Central Parietal Lobementioning
confidence: 99%
“…Alpha rhythms are typically observed during resting or idling states and are associated with consciousness and moderate activity. Beta rhythms, on the other hand, are often found in frontal or central areas [49,50] and are associated with spontaneous activity, such as problem-solving and attention [55]. Fig.…”
Section: H Band-pass Filtering and Frequency Band Separationsmentioning
confidence: 99%
“…However, the identification of EEG diagnostic biomarkers is complicated by the disorder's heterogeneity [25]. Chen et al [26], used evoked eventrelated potentials (ERP) during oddball P3 task. They found that healthy children recruited much stronger brain activity, mainly in the temporal and frontal regions, compared to ADHD children.…”
Section: Eeg Research Tools In Pediatric Adhdmentioning
confidence: 99%